Hypothalamic-pituitary-adrenal axis measures and cognitive abilities in early psychosis: Are there sex differences?. (October 2016) - Labad, Javier; Gutiérrez-Zotes, Alfonso; Creus, Marta; Montalvo, Itziar; Cabezas, Ángel; Solé, Montse; Ortega, Laura; Algora, Maria José; Sánchez-Gistau, Vanessa; Vilella, Elisabet
Highlights: We studied the role of sex, cortisol measures and cognition in early psychosis and healthy subjects. Cortisol awakening response (CAR) and diurnal cortisol slope were assessed. Dexamethasone suppression test (DST) was performed with 0.25 mg of dexamethasone. CAR was associated with poorer processing speed and verbal memory in female patients. A flattened diurnal cortisol slope was related to a poorer working memory in female patients. Abstract: Introduction: Measures of hypothalamic-pituitary-adrenal (HPA) axis activity such as increased diurnal cortisol levels or a blunted cortisol awakening response (CAR) have been associated with cognitive impairments in people with psychotic disorders. We aimed to explore whether there are sex differences in the relationship between HPA axis measures and cognition in early psychosis (EP). Methods: 60 EP outpatients and 50 healthy subjects (HS) were assessed with the MATRICS Consensus Cognitive Battery. Saliva cortisol levels were determined at the neuropsychological assessment and on another day at 6 sampling times: awakening; 30′ and 60′ post-awakening; and 10:00 h, 23:00 h and 10:00 h the day after the administration of 0.25 mg of dexamethasone, which occurred at 23:00 h. Three HPA axis measures were calculated: CAR, cortisol diurnal slope and cortisol suppression ratio of the dexamethasone suppression test (DST). Multiple linear regression analyses were conducted to explore the relationship between HPA axis measures and cognitive tasks while adjusting for covariates (education level, smoking, cannabis use, and cortisol levels at the cognitive assessment). Interactions between female sex, EP diagnosis and HPA axis measures were examined. Results: An increased CAR was associated with a poorer cognitive performance in EP women in processing speed and verbal memory. In contrast, a more flattened diurnal cortisol slope was associated with poorer functioning in the spatial working memory of EP women. DST suppression ratio was associated with better visual memory, without sex differences. Conclusions: Our study suggests that there are sex differences in the relationship between HPA axis measures and cognitive abilities in EP.